Improving Collaboration and Informatics Learning Outcomes through Flash Cards and the Joyful Learning Approach - Fikri, Kanzul Fikri Fauzi; Alfan, Muhammad; Agustyasari, Ratna (LifeSciFi, 2025)
The low level of student collaboration in Informatics learning presents a serious challenge that can hinder the achievement of optimal cognitive learning outcomes. A lack of cooperation causes students to struggle with sharing ideas, solving problems together, and developing a deep conceptual understanding. To address this issue, a Flash Card learning medium based on Augmented Reality (AR) was developed and integrated with a Joyful Learning approach. The aim is to create an enjoyable and interactive learning environment while enhancing student collaboration. This study employed a Research and Development (R&D) method using the ADDIE model in the development process. The resulting media was evaluated for feasibility and effectiveness through observations and learning outcome tests. Collaboration aspects were assessed using indicators such as communication, task distribution, decision-making consensus, and active engagement. The findings revealed that the AR-based Flash Card media significantly improved the learning outcomes of seventh-grade students in the Computer Systems topic, as evidenced by 93.3% of students scoring above the minimum passing grade, with an average score of 84.6. Additionally, the collaboration level reached 87.6%, categorized as “very good.” With interactive 3D visualizations and an enjoyable learning atmosphere, this media effectively supports Informatics learning in both cognitive and socio-affective aspects.